2022
DOI: 10.3390/en15093457
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia’s Vast Off-River Pumped Hydro Energy Storage Potential

Abstract: Indonesia has vast solar energy potential, far more than needed to meet all its energy requirements without the use of fossil fuels. This remains true after per capita energy consumption rises to match developed countries, and most energy functions are electrified to minimize the use of fossil fuels. Because Indonesia has relatively small energy potential from hydro, wind, biomass, geothermal and ocean energy, it will rely mostly on solar for its sustainable energy needs. Thus, Indonesia will require large amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Thus, the required storage was in the range 24-40 h of average consumption. This confirmed the estimation in previous work [36] that showed that with its low variability in terms of solar resources, Indonesia will require energy storage for daily use rather than for prolonged periods spanning weeks or months. On a per capita basis, the storage power and energy requirements were in the range of three kilowatts and 30-45 kWh, respectively.…”
Section: Energy Storage Requirementssupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the required storage was in the range 24-40 h of average consumption. This confirmed the estimation in previous work [36] that showed that with its low variability in terms of solar resources, Indonesia will require energy storage for daily use rather than for prolonged periods spanning weeks or months. On a per capita basis, the storage power and energy requirements were in the range of three kilowatts and 30-45 kWh, respectively.…”
Section: Energy Storage Requirementssupporting
confidence: 90%
“…In our previous works [12,36], we showed that Indonesia has enormous practical potential for solar generation (Section 3.1) and pumped hydro energy storage (Section 3.3). To put this potential in perspective, we note that the per-capita electricity consumption in advanced economies (European Union, USA, Australia, Japan, Singapore) is in the range 6-12 TWh per million people per year [37].…”
Section: Modelling Input and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With so many options, energy planners can afford to concentrate on those with the lowest likely costs per unit of storage. A total of 321 TWh of high-class off-river PHES was identified in Indonesia (Silalahi et al, 2022).…”
Section: Intermittency Of Solar Energymentioning
confidence: 99%